2021
DOI: 10.1038/s41598-020-80148-w
|View full text |Cite
|
Sign up to set email alerts
|

3D enamel profilometry reveals faster growth but similar stress severity in Neanderthal versus Homo sapiens teeth

Abstract: Early life stress disrupts growth and creates horizontal grooves on the tooth surface in humans and other mammals, yet there is no consensus for their quantitative analysis. Linear defects are considered to be nonspecific stress indicators, but evidence suggests that intermittent, severe stressors create deeper defects than chronic, low-level stressors. However, species-specific growth patterns also influence defect morphology, with faster-growing teeth having shallower defects at the population level. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…We found that deciduous teeth were less affected than permanent teeth. This has been reported in several other studies focusing on various mammals (Dobney and Ervynck, 1998;Lukacs, 1999;Bacon et al, 2018;Towle and Irish, 2019;McGrath et al, 2021), and several factors might explain this difference. First, in rhinocerotids, deciduous teeth develop partially (d1/D1 and d4/ D4) or totally (d2/D2 and d3/D3) in utero, which provides a relatively stable environment (Hitchins, 1978;Hillman-Smith et al, 1986;Böhmer et al, 2016).…”
Section: Enamel Hypoplasiasupporting
confidence: 71%
“…We found that deciduous teeth were less affected than permanent teeth. This has been reported in several other studies focusing on various mammals (Dobney and Ervynck, 1998;Lukacs, 1999;Bacon et al, 2018;Towle and Irish, 2019;McGrath et al, 2021), and several factors might explain this difference. First, in rhinocerotids, deciduous teeth develop partially (d1/D1 and d4/ D4) or totally (d2/D2 and d3/D3) in utero, which provides a relatively stable environment (Hitchins, 1978;Hillman-Smith et al, 1986;Böhmer et al, 2016).…”
Section: Enamel Hypoplasiasupporting
confidence: 71%
“…A short postnatal enamel formation period has been reported for a deciduous incisor of the Fumane 2 upper Palaeolithic modern human infant (39-42 ka) [29], which differs from longer enamel growth periods reported for extant humans [37]. Relatively rapid formation rates have also been reported for Neanderthal permanent anterior teeth [21,47].…”
Section: (A) Tooth Formation Rates and Timesmentioning
confidence: 82%
“…This is because defect margins are not always well-defined due to the curvature of the tooth and differences in perikymata widths within a defect (Hillson & Bond, 1997). Research using enamel depth profiles and/or micro-CT imaging may remedy the issue of subjective defect and duration identification (e.g., Cares Henriquez & Oxenham, 2020;McGrath et al, 2021;Xing et al, 2016). However, such methodology is associated with its own set of limitations because it requires specialized equipment that cannot usually be applied to larger bioarchaeological samples required for studies of FA, caused by restrictions from data collection and travel.…”
Section: Limitationsmentioning
confidence: 99%